Penggunaan Alat Bantu Pembelajaran untuk Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok pada Peserta Didik Kelas V SDN Ngadirejo 1 Kota Kediri Tahun Pelajaran 2024/2025 - Muhammad Alfian Lucky Jauharies; Rido Sejati; Sigit Prastyo; Faishal Dhedy Ramdhani; Ilham Maulana Riszxi; Wasilul Anwar (PT PUSTAKA CENDEKIA GROUP, 2025)
The purpose of this research was to improve the learning outcomes of the squat style long jump in class V students of SDN Ngadirejo 1 Kediri. This research is a classroom action research (PTK). This study was conducted in two cycles, with each cycle consisting of two meetings. The subjects of the study were 31 class V students of SDN Ngadirejo 1 Kediri consisting of 14 male students and 17 female students. Data sources came from teachers, students and researchers. Data collection techniques were through observation and documentation or archives. Data validity used data triangulation techniques. Data analysis used qualitative descriptive techniques using percentage techniques to see the tendencies that occurred in learning activities. The results of the data analysis can be presented as follows: the learning outcomes of students' squat style long jump in Cycle I from 31 students reached 51.61% or as many as 16 students had entered the completion criteria and in Cycle II it increased to 83.87% or as many as 26 students while 5 other students had not completed with a KKM score of 75. The results of the data analysis above can be concluded that the use of learning aids can improve the learning outcomes of squat style long jump in class V students of SDN Ngadirejo 1 Kediri.